DEVELOPING AND IMPLEMENTING A PEER MENTORSHIP PROGRAM TO ENHANCE NURSING TECHNICIANS’ CLINICAL REASONING SKILLS: A MIXED METHODS STUDY - Basheer Mordi Rajeh Alshammari, ‏Nawaf Dhahawi Rajan Aldhafeeri, ‏Khaloud falah ALshammari, ‏Mona Radhi ALbanaqi, ‏Anwar Hamdan Alsulobi, ‏Eidah mataq Aljamaili (Chelonian Research Foundation, 2022)
Clinical reasoning represents a pivotal yet challenging skill for nursing technicians to develop in order to provide safe, high quality care. This mixed methods study implemented and evaluated an intensive 6-month peer mentorship program pairing experienced and novice nursing technicians across medical-surgical units at a tertiary hospital in Saudi Arabia. The curriculum comprised experienced mentors demonstrating clinical reasoning approaches during care, guiding practice, and engaging mentees in reflective discussions during 72 dedicated clinical mentorship sessions. Clinical reasoning skills were assessed pre and post-intervention using validated case vignettes with a 5-point analytic rubric. Qualitative interviews elicited participants’ perceptions of the mentorship experience. Results showed significant reasoning skill gains from a mean of 1.9 to 4.1 on the rubric (p<0.001), progressing from novice to proficient levels. Interview themes emphasized enhanced reasoning, confidence, situational awareness, knowledge exchange, and deepened social connections from working closely with trusted peers. However, challenges coordinating busy schedules were noted. Study limitations include the single site and small sample. Overall, intensive peer mentorship shows promise as an applied skills development strategy to strengthen essential clinical reasoning capabilities within this integral healthcare provider group. Further research on efficacy and implementation factors can help refine programs tailored to nursing technicians’ learning needs and practice environments. Keywords: clinical reasoning, nursing technicians, peer mentorship, mixed methods